Important role of turbulent wind gust and its coherent structure in the rapid removal of urban air pollution. (1st July 2022) - Shi, Yu; Zeng, Qingcun; Liu, Lei; Cheng, Xueling; Hu, Fei
Abstract: The removal process of urban air pollution is very rapid even under the strong obstruction of various buildings in the city. In this study, based on high-accuracy ultrasonic anemometer observations at seven different altitudes on a 325 m tower, we proposed a physical mechanism in which turbulent wind gust and its coherent structure may play important roles in this phenomenon. Pollutants suspended within the urban canopy layer UCL cannot be quickly removed by means of basic flow but diffuse and crosse the UCL by means of the coherent structure of gust wind and then propagate further under strong basic flows above the UCL. With a continuous increase in wind speed in the whole layer, combined with gust-wind and turbulence mixing, the rapid transformation from heavily polluted days to clean days in urban areas can take place in just a few hours. Turbulent wind gust and its coherent structure were extracted by third-order Daubechies wavelet transformation. The downwind wind was decomposed into three separate components, basic flow u ¯ ( t ), gust-wind u ′ g ( t ), and turbulence u ′ t ( t ) . The results show that in the early rapid drop of urban surface pollutant concentration, horizontal wind speed at 8 m was still low, and sinking movements dominated in the lower layer. Friction velocity calculated from gust-wind u * g significantly affected the surface PM2.5 concentration, and was the most obvious factor with an inverse correlation coefficient −0.56. The correlation coefficient of coherent structure of gustiness Ru g w g at 8 m basically changed to positive values before the rapid decline of the surface PM2.5 concentration. The concentration of PM2.5 decreased significantly when Ru g w g > 0, and exhibited an increasing trend when Ru g w g < 0. The close relationship between the concentration of PM2.5 and Ru g w g indicated the important role of the coherent structure of gustiness in the rapid removal process of urban pollutants. The research deepens the vertical exchange process of matter and energy in the UCL, and provides a scientific reference for the rapid dissipation mechanism of urban air pollution.